PROFIL KONDISI MENTAL ATLET SEPAK BOLA DI KLUB AS ABADI KOTA PEKANBARU - Wahyudi, Wahyudi; Vai, Aref; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: The problem in this study is based on field observations on thefootball team at As Abadi Club, Pekanbaru City, the mental / psychological condition ofthe athletes has not been as expected, so it is very influential in the achievement ofathletes' achievements in soccer games. This study aims to determine how the profile ofthe mental / psychological condition of the soccer players in As Abadi Football Club,Pekanbaru City. The sampling technique was a sample population of 15 athletes. Basedon the results carried out from the calculation of the analysis, it can be concluded thatthe mental / psychological condition profile of the athlete can be categorized as "VeryGood", the results of the recapitulation of the scores obtained by all athletes inanswering all questions on the mental condition questionnaire are presented at 82.33%,where the value 82.33% are in the range of values (75.01% -100%) so that they can becategorized as "Very High". Where 13 athletes are in the range of values (75.01% -100%) so that they can be categorized as "Very High" and 2 athletes are in the range ofvalues (50.01% -74.00%) so that they can be categorized as "High". In the motivationfactor obtained a value of 89.56%, the confidence factor obtained a value of 83.89%,the concentration factor obtained a value of 82.89% so that it can be categorized as"Very high" and the emotional factor obtained a value of 73.00% so that can becategorized as "High".Key Words: Football, Mental, Emotion, Confidence, Concentration and Emotion